The forbidden zone for sleep is more robust in adolescents compared to adults - Monterastelli, Allison J.; Adams, John; Eastman, Charmane I.; Crowley, Stephanie J. (Frontiers in Sleep, 2024)
The propensity for sleep shifts later as puberty progresses. The present analysis examines whether the circadian-dependent wake maintenance zone, or forbidden zone for sleep observed in the evening just before habitual bedtime is more pronounced in late to post-pubertal adolescents compared to adults and may partly explain late sleep onset in maturing adolescents.Methods: 44 healthy late/post-pubertal adolescents (aged 14.3-17.8 years, 23 female) and 44 healthy adults (aged 30.8-45.8 years, 21 female) participated in an ultradian light/dark protocol for 3 days cycling between 2-hour wake periods (~20 lux) and 2-hour nap periods (~0 lux) without external time cues. The dim light melatonin onset (DLMO), a measure of circadian phase, was measured immediately before the ultradian protocol by sampling saliva every 30 min in dim light. Wrist actigraphs were used to assess sleep onset latency and total sleep time during the naps that occurred during the ultradian sleep/wake schedule. Sleep episodes were grouped into 2-hour bins relative to individual DLMOs (28-56 naps/bin). Sleep onset and total sleep time were compared between adolescents and adults as well as between males and females within each age group.Results: Adolescents took significantly longer to fall asleep compared to adults during naps that occurred in the 4h window surrounding the DLMO (2h before DLMO t(50)=2.13, p=0.04; 2h after DLMO t(33)=3.25, p=0.003). Adolescents also slept significantly less than adults during naps that occurred in the 4-h window surrounding DLMO (2 h before DLMO t(51)=-2.91, p=0.01; 2 h after DLMO t(33)=-1.99, p=0.05). Adolescent males slept less than adolescent females in naps that occurred in the 2 h window after the DLMO (t(14)=-2.24, p=0.04).Discussion: Compared to adults, late/post-pubertal adolescents showed greater difficulty falling asleep and maintaining sleep around the time of their DLMO, which usually occurs a few hours before habitual sleep onset. A greater amplitude in the circadian-driven forbidden zone for sleep could be an additional physiological mechanism explaining why maturing adolescents find it difficult to fall asleep early, increasing the risk for restricted sleep in the context of early school start times.